Thermohydraulic performance enhancement of a new hybrid duct solar air heater with inclined rib roughness. (March 2020) - Sivakandhan, C.; Arjunan, T.V.; Matheswaran, M.M.
Abstract: In this work, a new hybrid duct configuration of solar air heater is analytically investigated to improve the thermal performance of the system. The proposed design consists of parallel pass air flow paths with rectangular and triangular cross sections at upper and lower sides of the absorber plate. Both the sides of the absorber plates are roughened with inclined shape ribs. The roughness parameters are configured with relative roughness pitch at the bottom of the plate (Pb /eb ) of 4–16, relative roughness height of e/Dh ranges from 0.021 to 0.050 and relative angle of arc of (α/60) 0.5–1. Based on the analytical results it is concluded that the maximum effective efficiency is 80.1% for roughness pitch of 8, relative roughness height of 0.021 and relative angle of arc of (α/60) 0.5, at the mass flow rate of 0.045 kg/s at the upper and lower duct. The effect of the mass flow fraction (i) on the thermal performance of the solar air heater is also analyzed. The system improves the thermal and effective efficiency by 22.4% and 18.1% when compared to conventional rectangular duct parallel pass SAH. The design plots are developed to find the optimum values of roughness parameters with respect to ambient conditions. Highlights: A new hybrid duct solar air heater is proposed. Its thermal performance is analyzed by developing an analytical model. The influence of roughness parameters on the effective efficiency of the solar air heater is also investigated. The maximum enhancement in thermal and effective efficiency has 22.4 % and 18.1% in the mass flow rate of 0.045 kg/s.